Sources of Dietary Fiber and the Association of Fiber Intake with Childhood Obesity Risk (in 2–18 Year Olds) and Diabetes Risk of Adolescents 12–18 Year Olds: NHANES 2003–2006 - Mary Brauchla; WenYen Juan; Jon Story; Sibylle Kranz (Journal of Nutrition and Metabolism)
Increased fiber intake has been linked with lower risk of overweight and obesity in adults, but data are sparse for children. To address this issue, NHANES 2003–2006 data was used to evaluate (1) the food sources of fiber in children, (2) the dietary fiber density levels and risk of being classified as overweight/obese, and (3) the association between fiber intake level and impaired glucose metabolism in children. Analyses were restricted to the subsample of children with biological plausible diet reports (N=4,667) and stratified by 2–11 year olds (n=2072) and 12–18 year olds (n=2595). Results showed that the food sources are predominantly foods that are low in dietary fiber, but are consumed at high levels. In 2–18 year old plausible reporters, the risk for overweight/obesity decreased by 17% from children in the medium tertile of fiber density intake compared to the lowest tertile (OR=0.83, P value = 0.043) and by 21% between the highest compared to the lowest tertile (OR=0.79, P value = 0.031). There was a protective effect of being in the medium tertile of dietary fiber density (OR=0.68, P value <0.001) on impaired glucose metabolism. These results indicate a beneficial effect of higher fiber density in children’s diets.